Höffding step and beyond: The impact of visual sensory impairment on cognitive performance in neuropsychological testing of survivors of acute methanol poisoning - Bukacova, Katerina; Mana, Josef; Zakharov, Sergey; Diblík, Pavel; Pelclova, Daniela; Urban, Pavel; Klepiš, Petr; Klempíř, Jiří; Libon, David J; Růžička, Evžen; Bezdicek, Ondrej (NeuroRehabilitation, 2023)
BACKGROUND: Sensory deficits can result in limitations regarding how well neuropsychological test findings can be interpreted. Only a few studies have investigated the influence of vision alteration on neuropsychological tests. In 2012 the Czech Republic experienced mass methanol poisoning. Methanol metabolites cause histotoxic hypoxia to the optic nerve. OBJECTIVE: In the current study, the effect of the toxic damage on the parts of the visual pathway on visual and non-visual neuropsychological measures was investigated using electrophysiological methods (visual evoked potential (VEP) and optical coherence tomography (OCT) with retinal nerve fibre layer (RNFL) thickness measurement. METHODS: 53 individuals who experienced methanol poisoning participated in this research (76% men; ages 24 to 74 years, mean = 43.8±14.6 years; education 11.9±1.4 years). Each participant underwent comprehensive neurological, ophthalmological, and neuropsychological examinations. RESULTS: The results of mixed-effect models revealed significant small to a medium association between the Stroop test weak interference and Grooved Pegboard with the left eye global, nasal and temporal RNFL thickness. Also, medium associations between the Finger Tapping test and the Stroop test weak interference and left eye temporal RNFL, right eye temporal RNFL, and the latency P1 of VEP in the left eye were significant. CONCLUSION: The results of this study found a small to medium association (r = .15- .33; p = .010- .046) between RNFL thickness and cognitive visual test performance. Careful interpretation is suggested regarding results obtained from visual tests of the executive or motor functioning with participants with RNFL decrease or other types of early visual processing damage.
Keywords: Evoked Potentials, Visual; visual impairment; přežívající; Sensory deficit; methanol; Male; zrakové evokované potenciály; differential diagnosis; mužské pohlaví; Survivors; Methanol; Neuropsychological Tests; neuropsychology assessment; methanol poisoning; kognice; lidé; ženské pohlaví; Humans; neuropsychologické testy; Female; Cognition